1972
DOI: 10.1136/gut.13.7.528
|View full text |Cite
|
Sign up to set email alerts
|

The effects of humoral agents on the myoelectrical activity of the terminal ileum

Abstract: SUMMARY Electrical and motor activities of the terminal ileum have been recorded in 25 patients with a permanent ileostomy. Records made within a week of formation of the ileostomy show an increased motor activity which is significantly reduced after four weeks. Intravenous infusion of gastrin, 1 ,ug/kg-hr, was accompanied by a significant increase in action potentials and in the percentage motility. Conversely, secretin 1 unit/kg-hr was associated with a decrease in action potentials and in percentage motor a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1975
1975
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In his classic review, Davenport (14) cited Roman and colleagues, who demonstrated in the human duodenum, slow waves at a frequency of 11.2-12.6/min with superimposed action potentials (37). Slow waves in the human ileum were measured at 6.5-9.3/min (50). Several studies (8,21,47) reported that slow-wave frequency decreased from 11/min in the duodenum to 6/min in the human ileum.…”
Section: Myogenic Activitymentioning
confidence: 99%
“…In his classic review, Davenport (14) cited Roman and colleagues, who demonstrated in the human duodenum, slow waves at a frequency of 11.2-12.6/min with superimposed action potentials (37). Slow waves in the human ileum were measured at 6.5-9.3/min (50). Several studies (8,21,47) reported that slow-wave frequency decreased from 11/min in the duodenum to 6/min in the human ileum.…”
Section: Myogenic Activitymentioning
confidence: 99%
“…Radioimmunologic measurements of secretin and CCK indi cate that the active plasma concentrations of these hormones might be low (3,4,16). But, when lower doses than 0.5 U/kg/h of secretin were tested in man (27) or such low doses of CCK in animal experiments (18,24), these small amounts of the hormones were also active on the small intestine. These observations suggest that secretin and CCK are involved in the intricate mechanism modu lating the motor function of the gut.…”
Section: Discussionmentioning
confidence: 99%
“…Some workers have reported that pen-tagastrin results in a dose-dependent increase in the frequency of duodenal pacesetter potentials [44], while others have found that gastrin and pentagastrin cause no change in the frequency of the pacesetter potentials of the duodenum [45,46], jejunum [46], or ileum [47]. In contrast, most workers have confirmed Gregory and Tracy's early finding that gastrin stimulates contractions in the small intestine [27,[45][46][47][48][49]. Gregory and Tracy [27] showed that an intravenous bolus of gastrin causes rapid phasic contractions in the jejunum, after which a prolonged period of decreased tone occurs [27].…”
Section: Small Intestinementioning
confidence: 99%
“…Gregory and Tracy [27] showed that an intravenous bolus of gastrin causes rapid phasic contractions in the jejunum, after which a prolonged period of decreased tone occurs [27]. The stimulation of contractions is triggered by a gastrin-induced increase in small intestinal action potentials [45][46][47]. The influence of gastrin on intestinal transit has not been studied.…”
Section: Small Intestinementioning
confidence: 99%
See 1 more Smart Citation